Developing Assessment Skills of Prospective Primary School Teachers through Digital Assessment Tools (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the role of digital assessment tools in developing the evaluation skills of prospective primary school teachers. In the context of modern education, it is essential for future educators to master both traditional and technology-enhanced assessment methods. The study analyzes how platforms such as Google Forms, Kahoot, and Classkick can be effectively integrated into teacher training programs to enhance assessment literacy. Emphasis is placed on formative assessment, instant feedback, and data-driven decision-making as key components of digital competence. The findings suggest that the structured use of digital tools fosters a more engaging, accurate, and learner-centered assessment culture among pre-service teachers.